2012
DOI: 10.3126/jcmsn.v7i4.6735
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidities of elderly psychiatry out-patients in a tertiary-care hospital

Abstract: AbstractsWith the rise in life expectancy, the elder population is increasing. Morbidity profiles of elderly people may indicate different needs and priorities. This study aims to sort out referral pattern, attitude about psychiatric referral and morbidity profile among elderly psychiatric outpatients in a general hospital.A total of 100 consecutive elderly (>55 years) out-patients in psychiatry OPD coming into contact of the investigator and giving informed consent were enrolled. Diagnoses were made according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 4 publications
5
29
0
Order By: Relevance
“…They reported 30.7% of their geriatric psychiatric patient population had mood disorder, 28% had organic brain disorders and 9.3% was diagnosed as tension headache cases. In a 'psychiatric morbidities of elderly psychiatry out-patients' survey, at a tertiary-care hospital, Sakya reported major psychiatric diagnoses were mood (affective) disorder (46%), anxiety disorders (22%), substance use disorders (19%), organic and symptomatic psychiatric disorders (12%) and somatoform disorders (10%) 7 . In another psychiatric morbidity study Thapa …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They reported 30.7% of their geriatric psychiatric patient population had mood disorder, 28% had organic brain disorders and 9.3% was diagnosed as tension headache cases. In a 'psychiatric morbidities of elderly psychiatry out-patients' survey, at a tertiary-care hospital, Sakya reported major psychiatric diagnoses were mood (affective) disorder (46%), anxiety disorders (22%), substance use disorders (19%), organic and symptomatic psychiatric disorders (12%) and somatoform disorders (10%) 7 . In another psychiatric morbidity study Thapa …”
Section: Resultsmentioning
confidence: 99%
“…But, Koirala et al reported only 1.3% of their geriatric patients had a diagnosis of psychosis while Shakya reported the same rate as 6% 6,7 . While one epidemiologic survey found this rate to be 22.2% 5 , rates from various hospital-OPD based studies from India vary from 17% to 33% 9,18,19 .…”
Section: Psychosismentioning
confidence: 95%
See 2 more Smart Citations
“…[62][63][64] Whereas schizophrenia is less studied and published topic, 65 79 . This department has publications about child 80,81 and geriatric psychiatry 82 as well.…”
Section: Achievements In Mental Health Education and Trainingmentioning
confidence: 99%